Biology, health and environmental education for better citizenship: teachers’ conceptions and textbook analysis in 19 countries - Clément, Pierre (2007)
The European Biohead-Citizen research project has started in October 2004 and is now in its last year of implementation. It aims to understand how Biology, Health and Environmental Education can promote a better citizenship, by analysing potential differences in 19 countries (13 European countries and 6 non European countries) and associating them to controlled parameters. Six topics were defined by the consortium for the research (“Human Brain”, “Human Genetics”, “Human Origin”, “Human Reproduction and Sex Education”, “Health Education” and “Ecology and Environmental Education”). Specific grids were constructed and validated for application to primary to secondary school textbooks (5/6 to 17/18 years old students) of all 19 countries. A questionnaire was constructed and after validation in a pilot test, the final questionnaire was applied to a total of 6379 teachers of primary school and of secondary school (biology and of national language), and also to corresponding pre-service teachers. We describe the successive steps of both instruments (grids and questionnaire) collective construction process, their validation and application and also present general results to exemplify the diversity found in different countries textbooks and in teachers and future teachers’ conceptions. Teachers’ and future teachers’ conceptions are contrasted in relation to creationism, sexism views and awareness of some environmental issues. Some of these differences are correlated with the controlled parameters as religion, degree of religious practices, political positions, academic level and training type. Challenges of this interaction between the taught scientific knowledge, values and socio-cultural contexts will be discussed.